Pre-operative use of Lugol’s iodine in a case with toxic adenomatous goiter - Kulkarni, Sharang; Murchite, Sheetal; Parab, Saurabh; Tiwari, Vikash; Rajagopal, Archa (International Surgery Journal, 2021)
Euthyroid state is considered a requisite before planning a thyroid surgery. Before such a surgery, pharmacotherapy can be used for managing a hyperthyroid state. It warrants a long-term treatment with pharmacotherapy agents like imidazole class (carbimazole, methimazole) or propylthiouracil. In cases with large goiters, with pressure symptoms like dyspnoea, dysphagia, dysphonia; a surgeon would prefer a pharmacotherapy with a quicker action than the established agents. Lugol’s iodine was used pre-operatively before the advent of newer agents. In rural areas, where patients present with large goiters, hyperthyroid states due to lack of awareness and availability of the modern pharmacotherapy, Lugol’s iodine can be a rescue pre-operative therapy to make such a patient euthyroid and to decrease the vascularity of the goiter, which facilitates a safer thyroid surgery.